Exploring Teachers’ Perceptions of the Complex Contextual Factors Influencing Decisions to Participate in Professional Learning on Early Reading and Their Uptake of Classroom Strategies - Fairbrother, Michael (Université d'Ottawa / University of Ottawa, 2020)
Research demonstrates those who fail to learn to read well face unfair and lifelong societal disadvantage (Allington, 2011; Castles et al., 2018; Frontier, College, 2018). The number of children who fail to learn to read proficiently remains unacceptable and persists even as research suggests practices to help struggling readers (Allington, 2011; Castles et al., 2018). Building upon dismal findings from literacy networks and evidence from empirical research this study addresses this problem by exploring how contextual factors influence teachers’ learning and practice and student early reading achievement through two research questions: 1) How do contextual variables at the school, board and provincial level influence the planning, delivery and uptake of early reading professional learning opportunities? 2) How do teachers perceive the relationships between (a) their professional learning experiences, (b) their classroom early reading practices, and (c) student reading outcomes? This complexivist multiple instrumental case study explores the role of context upon teachers’ (N = 6) perspectives in three diverse schools (rural, urban and suburban) in one school board with the voices of principals (N = 3) and board-level reading experts (N = 3) providing additional layers of context. Within-case findings demonstrate the importance of meeting local teacher and student needs. Contextual networks represent pathways leading to learning, teaching and student reading development. Cross-case findings reveal the universal needs of the participants for meeting students’ core social and academic needs. Finally, a conceptual framework depicts the interaction of contextual factors within the teaching, learning and student achievement process. Theoretical, empirical and practical implications anchor a discussion proposing a research agenda situating teacher early reading learning into a professional learning collective compassionate to the learning needs of teachers who in turn can be more responsive to the local and universal needs of their students.
Keywords: Teacher learning; Early reading; Teacher change; Professional learning; Complexity theory; Qualitative research; Case study; Teacher knowledge; Learning systems; Literacy; Inclusion; Inclusive teacher learning